De la matière conquérante à la matière troublante - Ilona Woronow (Projets de Paysage)
The fascination for raw matter, essential in XVIIIth century science and philosophy, influences garden enthusiasts. Meantime, the interest in new artistic tendencies focuses their attention on development of original forms. Matter represents for them untouched nature, the objective of any landscape project of this time. By contrast, form connotes an artistic intervention which, according to the dissimulatio artis principle, must be concealed. Thus, theoretically, the coexistence of these two tendencies gives rise to a contradiction. What options will be left to the practicing gardener in his quest to tackle the gap between unprocessed material and artistic form ? An analysis of textual and iconographical period sources will help us understand the sites of resistance between the formal and the informal elements of the garden. We examine their relationship in three configurations : superimposition, mise en abyme and crystallization. To conclude, comparing the discourse on matter in both urban and rural settings allows us to interpret formal achievements as a response to the second facet of fascination – anxiety.